A Remark on the Homogeneity of Isosceles Orthogonality - Chan He; Dan Wang (Journal of Function Spaces)
Inspired by the definition of homogeneous direction of isosceles orthogonality, we introduce the notion of almost homogeneous direction of isosceles orthogonality and show that, surprisingly, these two notions coincide. Several known characterizations of inner products are improved.